Develop Students’ Awareness Toward Diabetes Through the English Primary Curriculum in UAE - Al Mulla, Kholoud Mohammed (2011)
This dissertation aims at developing a framework that could be integrated with the UAE English Language Teaching ELT curriculum of primary education. It concentrates on the health issues existing among UAE students especially diabetes. The main reason of conducting this research is that no recent research is found in UAE that discusses the causes of diabetes among young UAE nationals. Furthermore, it is evident that the UAE English curriculum does not highlight the subject of health education especially diabetes. The research has been conducted by using both primary and secondary sources. The secondary sources used are journals, articles, magazines, newspapers, online search engines, online databases, etc. The primary sources include different tools such as observations, note taking, visual studies, interviews and surveys. The research concludes that children in UAE have adopted poor eating and lifestyle habits which increases their chances of obesity and exposes them to the risk of diabetes. Moreover, the UAE curriculum fails to provide enough health education to students thereby enabling them to lead a healthy life. By incorporating diabetes awareness into the ELT curriculum schools should therefore implement various steps aimed at improving the health awareness among students and keeping them better informed about the diabetes ailment so that they are better equipped to fight it.